2001
DOI: 10.1046/j.1463-1318.2001.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term functional outcome following elective surgery for complicated sigmoid diverticular disease: sutured or stapled end-to-end anastomosis to the proximal rectum?

Abstract: These retrospective data suggest for the first time in the reported literature that hand-sewn colonic anastomosis to the proximal rectum provides a better short-term functional outcome than stapled anastomosis following elective resectional surgery for complicated sigmoid diverticulosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
7

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
2
0
7
Order By: Relevance
“…Reviewing 116 patients with end-to-end colorectal anastomosis to the proximal rectum after elective resection for complicated sigmoid diverticular disease, Sielezneff et al [14] found more stenoses in the patients who had stapled anastomoses than in those who had handsewn ones. They concluded that hand-sewn colonic anastomosis to the proximal rectum leads to the best short-term functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing 116 patients with end-to-end colorectal anastomosis to the proximal rectum after elective resection for complicated sigmoid diverticular disease, Sielezneff et al [14] found more stenoses in the patients who had stapled anastomoses than in those who had handsewn ones. They concluded that hand-sewn colonic anastomosis to the proximal rectum leads to the best short-term functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of stapled anastomosis has already been proven; however, stapling devices are expensive [15,21,26], are sometimes intraoperatively complicated by mechanical malfunction [13,15], and have a higher risk of anastomotic stenosis [22,29]. An extracorporal handsewn technique through a minilaparotomy has been used to perform colorectal anastomosis after sigmoid resection for diverticulitis, being proved to be safe and effective [26].…”
mentioning
confidence: 99%
“…Η αιμορραγία από την αναστόμωση προέρχεται από το βλεννογόνο του παχέος εντέρου και εκδηλώνεται συνήθως κατά την άμεση μετεγχειρητική περίοδο. [153][154][155] Η επιπλοκή αυτή της αιμορραγίας εκδηλώνεται με την εμφάνιση μέλαινας κένωσης ή αιματοχεσίας. Αιμορραγία στην αναστόμωση μπορεί επίσης να προκληθεί μετά από ανάπτυξη έλκους στην αναστόμωση.…”
Section: αιμορραγίαunclassified